Association between HDL Particles Size and Myeloperoxidase/ Paraoxonase-1 (MPO/PON1) Ratio in Patients with Acute Coronary Syndrome - Amirnader Emami Razavi; Gholam Basati; Jaleh Varshosaz; Soheila Abdi (Acta Medica Iranica, 2013)
Myeloperoxidase (MPO) and paraoxonase-1 (PON1) are inflammatory and anti-inflammatory enzymes, respectively that have been involved in the pathogenesis of coronary artery disease (CAD). In this study we sought to evaluate the relations of MPO and PON1 with high density lipoprotein (HDL) mean size in patients with acute coronary syndrome (ACS). Collectively, 50 control subjects and 50 patients with ACS were participated in this study. MPO level and PON1 activity was determined using immunoassay and colorimetric methods, respectively. HDL mean size was determined by a dynamic light scattering methodology. Other clinical risk factors were also determined by standard methods. The MPO/PON1 ratio amount was significantly higher in patients with ACS (1.49±1.10) than in control subjects (0.21±0.14) (P<0.01). There was a significant correlation between MPO/PON1 ratio and HDL mean size in patients with ACS. Amount of the enzymes and their relations to HDL particle size in patients with ACS may play a part in the pathogenesis of ACS. Also, MPO/PON1 ratio may be a robust predictor of ACS.